Modification of Classical Horseshoe Spillways: Experimental Study and Design Optimization - Hassanzadeh Vayghan, Vahid; Saber, Ali; Mortazavian, Soroosh (Civil Engineering Journal, 2019)
Investigation of the hydraulic aspects of spillways is one of the important issues regarding hydraulic structures. This study presents a modified horseshoe spillway (MHS) constructed by adding a flow passage and an internal weir in the bed of a classical horseshoe spillway (CHS). This modification increased the discharge efficiency and eliminated the rooster-tail hydraulic jump in CHSs. Eighteen laboratory-scale MHSs in various geometric sizes, six various CHSs, and a rectangular weir of the same width were constructed and tested under the same flow conditions. Results showed that in terms of discharge efficiency and water head reduction, CHSs and MHSs were superior to the rectangular weir. Compared to CHSs, the increased discharge flowrate in MHSs due to the internal weirs could further reduce the water head and thus increased their overall efficiencies. Design parameters effecting spillways’ discharge efficiencies were investigated based on dimensional analysis. The internal to external weir length ratio in MHSs was found to be a key design factor. To determine the optimal geometric design of CHS and MHS models, cubic polynomial models considering dimensionless parameters and their interactions were fitted to the experimental results. The cubic models revealed that higher discharge efficiencies in MHSs tended to occur at relatively low water heads and high internal to external weir lengths ratios.